Diagnostic Value of Cholinesterase Activity for the Development of Postoperative Delirium after Cardiac Surgery - Saha, Shekhar; Karaca, Kübra; Jebran, Ahmad Fawad; Waezi, Narges; Ort, Katharina; Brandes, Ivo; Hagl, Christian; Niehaus, Heidi (The Thoracic and Cardiovascular Surgeon, 2020)
Background Depression of cholinesterase (CHE) activity has been reported to lead to an amplified neuroinflammatory response, which clinically manifests as postoperative delirium (PD). This observational study investigates the association between CHE activity and the development of PD following elective cardiac surgery.Methods Patients with preexisting neurologic deficits or carotid artery disease as well as patients undergoing reoperations or procedures under circulatory arrest have been excluded from this study. The Mini-Mental State Examination, the Confusion Assessment Method for the Intensive Care Unit, and the Intensive Care Delirium Screening Checklist were performed at regular intervals. CHE activity was estimated pre- and postoperatively until postoperative day (POD) 5 and at discharge.Results A total of 107 patients were included. PD was diagnosed in 34 (31.8%) patients, who have been compared with those without PD. Time on ventilator, length of ICU, and hospital stay were longer in patients with PD (p = 0.001, p < 0.001, and p = 0.004, respectively). MMSE scores were lower in patients with PD (p < 0.001; p = 0.015). CHE activity on POD 1 to 4 as well as at discharge were lower in the delirium group (p = 0.041; p = 0.029; p = 0.015; p = 0.035; p = 0.028, respectively). A perioperative drop of CHE activity of more than 50% and a postoperative CHE activity below 4,800 U/L (on POD 0) were independently associated with an increased risk of development of PD (p = 0.038; p = 0.008, respectively).Conclusion In addition to the established functional tests, routine estimation of CHE activity may serve as an additional diagnostic tool allowing for the timely diagnosis and treatment of PD in cardiac surgery patients.
Keywords: postoperative delirium; cholinesterase activity; cardiac surgery